Multivariate base rates for the assessment of executive functioning among children and adolescents. Issue 6 (18th August 2019) - Cook, Nathan E.; Karr, Justin E.; Brooks, Brian L.; Garcia-Barrera, Mauricio A.; Holdnack, James A.; Iverson, Grant L.
ABSTRACT: This study provides observed base rates of low executive functioning test scores among healthy children and adolescents, stratifies those base rates by narrow intellectual functioning and age groupings, and provides normative classification ranges to aid the interpretation of performances on the Delis-Kaplan Executive Function System (D-KEFS) in clinical practice and research. Participants included 875 children and adolescents between 8 and 19 years old from the D-KEFS normative sample (48% male; 52% female). Among these participants, 838 had complete data and were included in the current study. The racial/ethnic composition of the sample was: White (73.7%), African American (12.4%), Hispanic (11.1%), and other racial/ethnic backgrounds (2.7%). The Overall Test Battery Mean (OTBM) and the prevalence of low scores at various clinical cut-offs were calculated for the 13 primary scores from the D-KEFS Trail Making Test, Verbal Fluency Test, and Color-Word Interference Test. The OTBM and base rates were also calculated separately for those scores reflecting executive functioning ( n = 7) and processing speed ( n = 6). Healthy children and adolescents commonly obtained low scores on the D-KEFS tests considered here. Younger age, lower estimated full-scale intelligence quotient, and more test scores interpreted were associated with a greater frequency of low scores. Clinicians and researchers are encouraged to consider these multivariate base rates when assessing and attempting to identify executive functioning impairment among children and adolescents with the D-KEFS.